Pardayev SOME PROBLEMS OF TRANSLATION ARTISTIC TEXTS: SOME PROBLEMS OF TRANSLATION ARTISTIC TEXTS - Pardayev, Mamasharif (Журнал иностранных языков и лингвистики, 2022)
The language and cultural barriers that arise when interpreting the original text by the translator. The main translation problems include: the specificity of the translation of set expressions; the problem of translating a play on words; cultural differences, while the main task of the translator is to eliminate emerging problems.